The Everyday Commoning Practices in Urbanising Localities - Bhuvaneswari Raman; Eric Denis (International Journal of the Commons)
Negotiating Rights to Inhabit Common Lands for Housing in Two Cities of South India This paper presents a framework for understanding the everyday political dynamics of commoning initiated by residents to secure their claims to ‘common land’ in urbanising localities. This paper puts forward the proposition that a spatialised approach would serve to reveal the extent to which unique socio-political and geographical factors exert an influence upon the dynamics of collective actions (commoning). It examines the experience of households in two squatter settlements on the outskirts of two South Indian cities: Villupuram, a medium-sized town in the state of Tamil Nadu, and Bangalore, a large metropolis in the state of Karnataka. It demonstrates how common land could serve as a foundation for the inclusion of poor communities within the city. The two cases presented in this paper reflect a trend observed in Indian cities since the mid-1990s, whereby rural common lands in urbanised localities, previously allocated to poor households for housing, have been targeted for more profitable development, eventually justified by environmental arguments. Consequently, those in poverty are compelled to compete with more powerful actors in order to assert their right to the common land they occupy for the purpose of housing. The two case studies demonstrate the capacity of such communities to unite and engage in practical political actions to regularise their settlements and dwellings. We describe their engagement with multiple government institutions across the rural and urban continuum and illustrate the influence of contextual factors, including geographical and temporal factors, in shaping the unique and diverse trajectories of commoning.